The effect of grape products containing polyphenols on oxidative stress: a systematic review and meta-analysis of randomized clinical trials - Sarkhosh-Khorasani, Sahar (Nutr J, 2021)
BACKGROUND: The literature showed that Grape Products Containing Polyphenols (GPCP) had anti-oxidant activity. However, the effects of GPCP on different biomarkers of oxidative stress are still controversial. In this regard, this systematic review and meta-analysis aimed to evaluate the effect of Grape Products Containing Polyphenols (GPCP) intake on oxidative stress markers. METHODS: PubMed, Scopus, Web of Science, and Google Scholar data bases were searched up to August 20, 2020. A random-effects model, weighted mean difference (WMD), and 95% confidence interval (CI) were applied for data analysis. Meta-analysis was conducted over 17 eligible RCTs with a total of 633 participants. The study registration number is CRD42019116696. RESULTS: A significant increase was observed in Total Antioxidant Capacity (TAC) (weighted mean difference (WMD) = 1.524 mmol/L, 95% confidence interval (CI): 0.83, 2.21). Intake of GPCP enhanced Superoxide Dismutase (SOD) (WMD = 0.450 mmol/L, 95% CI: 0.23, 0.66), TAC (WMD = 2.829 mmol/L, 95% CI: 0.13, 5.52), and Oxygen Radical Absorbance Capacity (ORAC) (WMD = 0.524 μmol/L, 95% CI: 0.42, 0.62) among healthy participants. Higher GPCP doses increased SOD (WMD = 0.539 U/mgHb, 95% CI: 0.24, 0.82) and ORAC (WMD = 0.377 μmol/L, 95% CI: 0.08, 0.67), whereas longer intervention periods enhanced ORAC (WMD = 0.543 μmol/L, 95% CI: 0.43, 0.64). CONCLUSION: GPCP intake may partly improve status of oxidative stress, but further well-designed trials are required to confirm these results. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12937-021-00686-5.